Postural stability, risk of falls and fear of falling in elderly with diabetic neuropathy who do therapeutic exercises - Hudson Azevedo Pinheiro; Karla Helena Coelho Vilaça; Gustavo de Azevedo Carvalho (Universidade de São Paulo, 2014)
This study aimed to analyze postural stability, the risk of falls and fear of falling in elderly with diabetic neuropathy (DNP) that perform therapeutic exercises. The authors conducted the screening of elderly patients with DNP using the instruments Neuropathy Symptom Score (NSS) and the Neuropathy Disability Score (NDS). The 50 selected patients were divided into two groups: 24 of G1 (who were performing therapeutic exercises) and 26 of G2 (the control group). To assess postural stability, risk of falls and fear of falling among groups used the pressure platform, the Berg Balance Scale (BBS) and the Falls Efficacy Scale (FES-I). There was no significant difference in the outcome of BBS scales (p=0.16) and FES-I (p=0.15) between the G1 and G2; by the pressure platform, we found differences between G1 and G2 in parameters path length (PL) and stability medio-lateral (ML), with both eyes closed (EC). Elderly people with DNP who perform therapeutic exercise have better stability and ML and PL with EC that sedentary elderly; however, there was no association with therapeutic exercise, risk of falls and fear of falling.